Facile ultrasound route for the fabrication of green emitting Ba2SiO4:Eu2+ nanophosphors for display and dosimetric applications. (January 2018) - Venkataravanappa, M.; Nagabhushana, H.; Darshan, G.P.; Sharma, S.C.; Archana, K.V.; Basavaraj, R.B.; Prasad, B. Daruka
Graphical abstract: Highlights: Simple ecofriendly sonochemical method was used for the synthesis of Ba2 SiO4 :Eu 2+ using EGCG bio-surfactant. Various morphologies were obtained by tuning the reaction parameters. PL emission spectrum showed broad peak around ∼505 nm. The effect of γ-dose on the TL intensity was studied and for 3 kGy gamma-dose the TL intensity was found to be maximum. CIE and CCT results exhibit the phosphors were quite useful for the fabrication wLEDs. Abstract: A series of Eu 2+ (1–5 mol%) activated Ba2 SiO4 nanophosphors were prepared by ecofriendly ultrasound assisted sonochemical route using Epigallocatechin gallate (EGCG) extract as bio-surfactant. The obtained nanophosphors were well characterized by Powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) etc. The average crystallite size was estimated using Debye–Scherer's formula and Williamson–Hall (W–H) plots and were found to be in the range 20–32 nm. The photoluminescence excitation spectrum exhibited two broad bands around 330 and 370 nm ascribed to the transitions of Eu 2+ from 4f-ground state to 5d-excited state. The emission spectra showed broad band around 505 nm wavelength ascribed to 5d → 4f allowed transition of Eu 2+ ions. Thermoluminescence (TL) of Eu 2+ doped Ba2 SiO4 nanophosphors were investigated using γ-irradiation in the dose range1–6 kGy at a warming rate of 5 °C min −1 . The phosphors show a well resolved single glow peak at ∼175 °C. The TL intensity of 155 °C glow peak increase linearly with γ-dose and room temperature fading was ∼76% which was highly useful in radiation dosimetry. The kinetic parameters ( E, s ) were estimated and the results were discussed. The chromaticity co-ordinates of all the prepared phosphors were located in green region, as a result Eu 2+ activated Ba2 SiO4 was a promising single phased phosphor for WLEDs.